Evaluation of result of plate augmentation and autogenous bone grafting for femoral shaft nonunion after locking nail - Ho , Van Thanh; Truong Tri Huu (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
Introduction: The method of treatment for nonunion of the femoral shaft fracture after locked intramedullary nail fixation is challenging. The methods of exchanging an existing nail with a larger-sized nail, dynamization, removal of the nail followed by locking plating, and bone grafting have all been reported. In our study, we used plate augmentation and iliac bone grafting with retention of the nail. Objectives: The purpose of our study was to evaluate the effectiveness of this method in treating femoral shaft nonunion after open reduction and internal fixation with locked intramedullary nail fixation. Methods: This is a retrospective descriptive study and longitudinal research. Between January 2017 and January 2019, 32 patients who had nonunion after open reduction and internal fixation with locked intramedullary nail for femoral shaft fracture were included in our study. There were 23 men and 9 women participants, with a mean age of 32 years (range, 16-60 years old). The mean period of follow-up after surgery was 13 months. The patients were classified into three groups: atrophic, oligotrophic, and hypertrophic. We retained the nail and performed plate augmentation for all patients, with simultaneous autologous bone grafting harvested from the iliac crest. We followed up on all patients with plain X-ray film examination and assessed functional recovery status to determine osseous union condition. SPSS 20.0 software was used for this descriptive statistical analysis. Results: All 32 of the patients achieved postoperative bony union uneventfully at a mean time of 13 months (range, 10-20 months). The mean operative time was 65 minutes, and the mean blood loss was 150 ml. All of the patients could walk bearing full weight without pain within 3 months. There were no significant complications such as broken hardware, implant back-out, axial or rotational malalignment, or deep infections. Conclusion: Plate augmentation with retention of the nail and autologous bone grafting may be an effective and reliable alternative in treating nonunion of the femoral shaft fracture after open reduction and internal fixation with locked intramedullary nail.